Sosialisasi dan Implementasi Ejaan Bahasa Indonesia yang Disempurnakan untuk Perbaikan Penamaan bagi Villa di Wisata Kemuning, Karanganyar, Jawa Tengah - Kundharu Saddhono; Muhammad Rohmadi; Budhi Setiawan; Raheni Suhita; Ani Rakhmawati; Sri Hastuti (Universitas 45 Surabaya, 2024)
The Enactment of Law No. 24 of 2009 concerning the Flag, Language, and State Emblem and National Anthem which is emphasized by Government Regulation No. 57 of 2014, Regulation of the Minister of Education and Culture No. 42 of 2018, and Decree No. 0424/I/BS.00.01/2022 must of course be obeyed by all Indonesian citizens. Public obedience to the law is still low, especially related to language. For example, many place names in public areas still use foreign languages. It is clear that the use of language violates the law, especially with regard to language. Enforcement of the law must be spearheaded by the government itself. If the community can obey the law, socialization to the general public will be smoother. Governance in government and private agencies is one of those regulated in the Law, especially Article 33 paragraph 1 which reads